The “genetic erosion” of the soil ecosystem - Giuseppe Lo Papa; Vanessa Palermo; Carmelo Dazzi (International Soil and Water Conservation Research, 2013)
This paper takes into consideration the influence of human activities on the loss of pedodiversity in a Mediterranean area due to large scale farming. In particular it examines the quantitative and qualitative soil changes in a period of 53 years (from 1955 to 2008) evaluating the loss of soil diversity at soil subgroups level of the USDA Soil Taxonomy system. The following indices were used: richness; Shannon’s diversity index; Simpson diversity index; Shannon’s evenness index; Simpson’s evenness index. In this case study, considering what we observed in time, the human intervention in soil transformation could increase the diversity in the landscape in an initial phase, but forwarding by large scale farming the result is a huge loss of pedodiversity in time, as diversity indices remarkably have shown. This analysis enabled identification of disappeared soil types, with their unique history of formation. In our opinion this strongly reflects a sort of “genetic erosion” of the soil types, resulting in a substantial weakening of the whole pedo-ecosystem.